Sorting things out: valuation of new firms in uncertain markets - Sanders, Wm. Gerard; Boivie, Steven (Strategic Management Journal, 2004)
Abstract New business models combined with a lack of objective operating data result in significant information asymmetry and uncertainty in the valuation of new firms in emerging markets. Information asymmetry increases the risks of both adverse selection and moral hazard. When traditional differentiators of firm quality are lacking, such as in emerging economic sectors, markets may turn to secondary information sources to filter and sort firms. We investigate the roles played by observable corporate governance characteristics as indirect indicators of new firms' potential qualitative differences. Markets may sort firms based on such characteristics because they are perceived to be correlated with desired but unobservable characteristics and actions and they lower the risks of both adverse selection and moral hazard. Our study of publicly traded U.S. Internet firms found that firm market valuation was strongly associated with corporate governance characteristics (e.g., executive and director stock‐based incentives, institutional and blockholder stock ownership, board structure, and venture capital participation). In addition, firm age moderated how markets used some quality proxies to determine firm valuation during the post‐IPO period. Copyright © 2003 John Wiley & Sons, Ltd.